Text memorization: An effective strategy to improve Chinese EFL learners’ argumentative writing proficiency - Wang, Qunfeng (Frontiers in Psychology, 2023)
This study aims to explore the impact of text memorization strategy on Chinese EFL learners’ English argumentative writing proficiency, the process of their text memorization and specific strategies deployed for the enhancement of memorization effect. Seven text memorization tests, one pre-test and one post-test were administrated to 33 Chinese English majors to respectively examine students’ memorization outcome as well as their English argumentative writing proficiency before and after memorization of seven model English writings. Data were also collected by interviews with 12 top scorers in text memorization tests. The results showed that text memorization as a foreign language learning strategy impacted significantly on the improvement of EFL learners’ argumentative writing proficiency. Moreover, in the text memorization process in which varieties of strategies were employed, it was found that storage was preceded by understanding among the majority of the interviewees. Since text memorization was advantageous to EFL learners’ writing proficiency, a new system of text memorization strategies was developed in the current study to provide both scholars and teachers with insights about text memorization strategies associated with EFL learners’ writing skill.